Проблеми та перспективи ринку злиття та поглинання в Україні - Тарасова, О. В. (Видавництво Львівської політехніки, 2010)
Предметом аналізу в статті є процеси злиття та поглинання (M&A) компаній в Україні. Розглянуті особливості цього процесу, проаналізовано основні напрями та виокремлені існуючі проблеми в нашій країні. Запропоновано шляхи подолання основних проблем. Визначені перспективи та тенденції ринку M&A в Україні. The processes of merger and acquisitions (M&A) of companies in Ukraine are the article of analysis in the article. Considered features of the given process, basic directions are analysed and selected existing problems in our country. The ways of overcoming of basic problems are offered. Prospects and market tendencies of M&A in Ukraine are certain.
Challenges and prospects of market mergers and acquisitions in Ukraine
Keywords: злиття та поглинання компаній; процеси злиття та поглинання; ринок M&A в Україні; mergers and acquisitions; mergers and acquisitions; M & A market in Ukraine